VIRTUAL PERFORMANCE SPACES AND THE FUTURE OF LIVE ART EXPERIENCES - Dhanalakshmi V; Shanthi P; Damodaran B; Bharathi M, Nishaa; Vijaya T, Veda; Xinwen, Cheng (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The rapid evolution of digital technologies caused the radical shift of the environment of performing arts and new virtual performance spaces were developed that are transforming the manner in which live art experiences were being developed, delivered, and experienced. Traditional performing arts have always been premised on the physical space and close association between the acting and the audiences. However, in recent years, the development of immersive technologies, including, virtual reality (VR), augmented reality (AR), mixed reality (MR), motion capture systems, spatial audio technologies, and cloud-based streaming devices has made it possible to create dynamic virtual space and expand the limits of artistic expression to the stage. In this paper, the concept of virtual performance space and its role in revolutionizing the future of live performance of art will be discussed. The paper includes the review of literature of the present research on digital performing arts and review of the technologies which are involved in creating the illusion of immersible virtual performance environments. Various digital performance platforms, including live streaming platforms, virtual theatre platforms, and metaverse environments, are evaluated through the comparative analysis with the following criteria being evaluated: immersion, accessibility, interaction with the audience, scalability, and flexibility of production. Based on this discussion, it is proposed that a conceptual design of the virtual performance spaces be developed, comprising of the integration of immersive media technologies, interactive tools of audience participation and cloud based distribution infrastructures. Besides, the provided framework is predicted to be utilized in serving the whole lifecycle of digital performance production, including content creation and virtual staged design, real-time engagement with the audience and performance analytics